Pengaruh Film Animasi Terhadap Peningkatan Kemampuan Bahasa Anak Usia 4-5 Tahun di Paud Taroto Jaya Dusun Bantu Desa Bantulanteh Sumbawa - Suci Sukmawati; I Made Suwasa Astawa; Baik Nilawati Astini; Nurhasanah Nurhasanah (Indonesian Publication Center, 2021)
This research is motivated by the lack of development of language skills and learning media used in improving children’s language skills. This study was conducted to determine the effect of animated films on improving the language skills of children aged 4-5 years in PAUD Taroto Jaya, Bantu Village, Bantulanteh Village. This study uses a quantitative method of Pre experimental design experiment with a one group pre-test post-test design. The sample in this study were children aged 4-5 years in PAUD Taroto Jaya Dusun Bantu Sumbawa, a total of 21 people consisting of 13 girls and 8 boys. Sampling in this study used non-probability sampling where all members of the population were used as samples. Data collection techniques using observation sheets and documentation. The analysis technique includes normality test, hypothesis testing, and statistical hypothesis. The results showed that there was a significant effect on language skills of 0.000, smaller than 0.5 (0.000 < 0.05), which means that the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted. In conclusion, there is a significant effect of the use of animated films Nussa and Rara on improving the language skills of children aged 4-5 years, so that the use of animated film as learning media can be maintained to improve children’s language skills.